Electropherotypes and G-Types of Group A Rotaviruses Detected in Children with Diarrhea in Lagos, Nigeria. (17th December 2013) - Ayolabi, Christianah Idowu; Ojo, David Ajiboye; Armah, George Enyimah
Abstract : Approximately over 500, 000 children die annually due to severe dehydrating diarrhea caused by rotaviruses. This work investigated rotavirus infection among children less than 5 years with diarrhea in Lagos and determined the circulating electropherotypes and genotypes of the virus isolates. Three hundred and two (n = 302 ) stool samples from children below 60 months were collected from different hospitals and health care centers in Lagos and subjected to enzyme immunoassay (EIA) to determine the presence of Group A rotavirus, RT-PCR to determine the G-types, and polyacrylamide gel electrophoresis (PAGE) to determine the electropherotypes. The results show that 60.3% of the samples showed distinct rotavirus RNA migration pattern, having long electropherotypes (55.3%) of seven variations dominating over the short electropherotypes (44.5%). Six different G-types were detected (G1, G2, G3, G4, G9, and G12). Serotypes G1 and G12 showed long electropherotypic pattern while G2, G3, and G9 exhibited either short or long electropherotype. All G4 detected show short electropherotypic pattern. In conclusion, information on the genomic diversity and RNA electropherotypes of rotaviruses detected in children with diarrhea in Lagos is reported in this study.